2016
DOI: 10.1370/afm.1934
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Clerks in the Patient-Centered Medical Home

Abstract: Research evaluating the effectiveness, function, and implementation of patientcentered medical homes (PCMHs) has found major socioprofessional transformations and contributions of primary care physicians and, to a lesser degree, nurses. Our longitudinal ethnographic research with teams implementing PCMH in Veterans Health Administration (VHA) primary care identifies the important but largely under utilized contributions of clerks to PCMH outcomes. Although the relationship of high-performing clerical staff to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…25 Such care team members include clinical and nonclinical professionals as well as family members with specific, defined roles and dedicated time and effort specific to care planning. 26 Staff roles and contributions should be defined and understood by all members. 27 Ensuring that team members work to the "top of their license" fosters cost-effectiveness and efficiency.…”
Section: Infrastructure For Care Coordination and Planningmentioning
confidence: 99%
“…25 Such care team members include clinical and nonclinical professionals as well as family members with specific, defined roles and dedicated time and effort specific to care planning. 26 Staff roles and contributions should be defined and understood by all members. 27 Ensuring that team members work to the "top of their license" fosters cost-effectiveness and efficiency.…”
Section: Infrastructure For Care Coordination and Planningmentioning
confidence: 99%
“…Using clerks to introduce PHP, as one site in our study did, may help orient patients and unburden busy providers while achieving a key PCMH goal of optimizing staffs' responsibilities. 35 We found that PHP adoption required an integrated, team-based approach consistent with the PCMH model 36,37 for its successful incorporation into clinical care. Sites in our study took two overarching approaches to incorporating PHP in teams: one spread responsibility; the other centralized responsibility among health coaches.…”
Section: Discussionmentioning
confidence: 89%
“…26 In contrast to findings about burnout among the other clinical staff, the observation that higher degrees of reported burnout among MSAs were associated with better perception of access may reflect the greater workload required to respond quickly to patient requests for appointments. 27,28 Open access was most strongly correlated with better patient perception of access. Staff reporting their clinic furnished open access could indicate staff perception of the clinic as "good" for access, in alignment with patient perception.…”
Section: Discussionmentioning
confidence: 94%